Адміністративні послуги в діяльності сервісних центрів МВС України : автореф. дис. - Князюк, О. Г.; Kniaziuk, O. H.; Князюк, А. Г. (Харків : Харківський національний університет внутрішніх справ, 2021)
Дисертацію присвячено визначенню поняття, видів та особливостей надання адміністративних послуг сервісними центрами МВС України. У дослідженні викладено сучасний погляд на розуміння змісту адміністративної послуги як предмета діяльності сервісних центрів МВС України як комплексної юридичної категорії з дуалістичною природою, що використовується для позначення соціально-корисної діяльності спеціалізованих суб’єктів, яка здійснюється з метою реалізації прав, свобод і законних інтересів фізичних та юридичних осіб шляхом втілення результату владних повноважень сервісних центрів МВС України та забезпечення умов, необхідних для реалізації процедур надання таких послуг. Визначено та проаналізовано ознаки, які характеризують адміністративні послуги як предмет діяльності сервісних центрів МВС України. З’ясовано місце сервісних центрів МВС України в системі суб’єктів надання адміністративних послуг. Окреслено правові засади та принципи надання адміністративних послуг сервісними центрами МВС України, та місце серед них норм адміністративного законодавства. Сформульовано поняття та окреслено процедуру надання дозвільних, реєстраційних та інформаційних адміністративних послуг сервісними центрами МВС України. Узагальнено зарубіжний досвід надання адміністративних послуг у правоохоронній сфері та запропоновано напрями його впровадження в діяльність сервісних центрів МВС України. Визначено адміністративно-правові критеріїоцінки ефективності процедури надання адміністративних послуг сервісними центрами МВС України.

This thesis is devoted to the definition of the concept, types and features of providing administrative services by the service centers of the Ministry of Internal Affairs of Ukraine. The study outlines a modern view of the public service content definition as a subject of activities of the service centers of the Ministry of Internal Affairs of Ukraine, as a complex legal category with dualistic nature, used to denote the socially useful activities of specialized entities, carried out in order to implement the rights, freedoms and legitimate interests of individuals and legal entities by implementing the result of power of the service centers of the Ministry of Internal Affairs of Ukraine and ensuring conditions necessary to realization the procedures of providing such services. The signs characterizing administrative services as a subject of the service centers of the Ministry of Internal Affairs of Ukraine activity are defined and analyzed. The place of the service centers of the Ministry of Internal Affairs of Ukraine in the system of subjects providing administrative services is clarified. The legal basis and principles of providing administrative services by the service centers of the Ministry of Internal Affairs of Ukraine and the place of the administrative legislation norms among them are determined. The concept and the procedure for the provision of permissive administrative services by the service centers of the Ministry of Internal Affairs of Ukraine are formulated and outlined. The term, characteristics and procedure of providing registration administrative services by the service centers of the Ministry of Internal Affairs of Ukraine are defined. The content and procedure of providing information administrative services by the service centers of the Ministry of Internal Affairs of Ukraine are disclosed. Foreign experience in the provision of administrative services in the law enforcement sphere is summarized and the directions of its implementation in the activities of the service centers of the Ministry of Internal Affairs of Ukraine are proposed. Administrative and legal criteria for assessing the effectiveness of the providing procedure of administrative services by the service centers of the Ministry of Internal Affairs of Ukraine are formulated. Scientific and theoretical conclusions and practical proposals aimed at improving the legislation, the norms of which regulate the procedure for providing administrative services by the service centers of the Ministry of Internal Affairs of Ukraine are substantiated.

Диссертация посвящена определению понятия, видов и особенностей предоставления административных услуг сервисными центрами МВД Украины. В исследовании изложен современный взгляд на понимание содержания административной услуги как предмета деятельности сервисных центров МВД Украины как комплексной юридической категории с дуалистической природой, которая используется для обозначения социально-полезной деятельности специализированных субъектов, осуществляемой с целью реализации прав, свобод и законных интересов физических и юридических лиц путем реализации результата властных полномочий сервисных центров МВД Украины и обеспечения условий, необходимых для реализации процедур предоставления таких услуг. Определены и проанализированы признаки, характеризующие административные услуги как предмет деятельности сервисных центров МВД Украины. Выяснено место сервисных центров МВД Украины в системе субъектов предоставления административных услуг. Обозначены правовые основы и принципы предоставления административных услуг сервисными центрами МВД Украины и место среди них норм административного законодательства. Сформулировано понятие и определена процедура предоставления разрешительных, регистрационных и информационных административных услуг сервисными центрами МВД Украины. Обобщен зарубежный опыт предоставления административных услуг в правоохранительной сфере и предложены направления его внедрения в деятельность сервисных центров МВД Украины. Определены административно-правовые критерии оценки эффективности процедуры предоставления административных услуг сервисными центрами МВД Украины.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Administrative services in activities of the service centers of the Ministry of Internal Affairs of Ukraine
Князюк, О. Г. Адміністративні послуги в діяльності сервісних центрів МВС України : автореф. дис. ... канд. юрид. наук : 12.00.07, 081 / Князюк Олександр Григорович; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2021. - 27 с.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; Україна. Ukraine. Украина; 12.00.07; 081 – Право; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; адміністративні послуги; administrative services; административные услуги; інформаційні послуги; information services; информационные услуги; сервісні центри МВС; Service Centers of the Ministry of Internal Affairs; сервисные центры МВД; дозвільні послуги; permitting services; разрешительные услуги; реєстраційні послуги; registration services; регистрационные услуги; адміністративно-правові критерії; administrative and legal criteria; административно-правовые критерии